Seismic vulnerability study of guillemard railway bridge - Teow, Ching Ching (2008)
Malaysia is surrounded by countries that had experienced many great earthquakes. Records have shown that we do sometimes experience some off-set tremors originating from the Indonesian zone. Therefore it would be unwise to totally ignore the effects of earthquakes on structures. The purpose of this study is to present the results of the case study of the earthquake response on the Guillemard Railway Bridge. The bridge had been remodeled using SAP 2000. The behavior of Guillemard Railway Bridge under the earthquake loading can be obtained by analyzing the Free Vibration Analysis, Time History Analysis and Response Spectrum Analysis with different levels of ground acceleration (0.074g, 0.15g, 0.25g and 0.35g), in different directions (x, y, z). Moment and shear force capacities for each element are calculated to enable comparison to be made between element capacity and element loading. The purpose is to check to what extend Guillemard Railway Bridge could survive under different ground acceleration and to identify the critical part of the bridge under earthquake loading. From the results, it is noticed that the column failure could occur even in low intensity earthquake acceleration. Deck failure is caused by its inability to hold the design ultimate resistance moment of earthquake loading. Earthquake which happens in horizontal transverse direction has very little effect to the seismic performance of the bridge deck. The bridge deck may fail when earthquake happens in vertical direction, under all various earthquake intensities. For horizontal longitudinal earthquake direction, the bridge deck is safe up to 0.15g earthquake intensity. The most earthquake-vulnerable part of Guillemard Railway Bridge is the fourth span and the fourth pier. Moreover, the top chords at the highest point of the truss and the connection between the spans also most likely to be vulnerable if earthquake occur.